Analisis Hukum Islam Terhadap Transaksi Jual Beli Cincin Beserta Batunya di Toko Emas Sami Purworejo - Muhajir Muhajir; Sahlan Sahlan; Arief Setiawan (Jurnal Ilmiah Ekonomi Islam, 2022)
Buying and selling gold and gemstones is a lot happening in every gold shop, because one of the ways someone invests for the future is to buy gold. In this discussion, the author aims to review the practice of buying and selling rings and their stones at the Sami Gold Shop Jl. Ahmad Dahlan 168 Purworejo District. The writing of this thesis uses qualitative research using a normative approach, namely approaching investment problems with Islamic law. The research method used is field research (Field Research) in order to obtain data obtained from the field. Based on the results of this study it can be concluded that the implementation of buying and selling gold and gemstones at the Sami Gold Shop Jl Kh Ahmad Dahlan 168 Purworejo is not legal under Islamic law, because it is detrimental to one of the parties, gharar and also the seller does not want to know because the buyer does not agree. by selling like that to the detriment of the buyer. Keyword : Gold Buying and Selling, Jewelry, Islamic Law